Addressing student cynicism through transformative learning - Duarte, Fernanda (Journal of University Teaching and Learning Practice, 2010)
This paper reflects on insights that emerged from the findings of a qualitative study conducted by the author in 2007 with third year management students from an Australian university on their perceptions in relation to business ethics. The findings revealed an attitude of cynicism with regard to the application of ethical principles beyond university years – in “the real world of business'. This led the author to engage in more systematic efforts to address this problem, and to this end, she found Mezirow's notion of transformative learning inspiring and valuable. It is contended that reflection and critical thinking are crucially important skills to enable consciousness shifts that will lead to a deeper understanding and greater appreciation of the importance of ethical conduct in management. They can act as antidotes to attitudes of cynicism which make students feel powerless and dejected, disinclined to apply the knowledge gained during their training beyond university years. A selection of examples of class activities and assessments to foster transformative learning is provided.